The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/anec.12966
|View full text |Cite
|
Sign up to set email alerts
|

Association between complete right bundle branch block and atrial fibrillation development

Abstract: Atrial fibrillation (AF) is a common cardiac arrhythmia in the general population (Kjerpeseth et al., 2021) and is associated with increased cardiovascular morbidity and mortality. (Tanaka et al., 2021) Early recognition of AF could allow for more successful control of arrhythmia and protect the patient from adverse consequences. (Hindricks et al., 2021) Therefore, it is crucial to identify patients who are at an increased risk of developing AF. Complete right bundle branch block (CRBBB) is one of the most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Several studies have examined risk factors for AF, which could be found using ECG. Interatrial, first-degree atrioventricular (AV), and right bundle branch blocks are reportedly risk factors for the incidence of AF [38][39][40] . ECG measurements and findings, such as PAC, p wave, and LVH, are reportedly risk factors for the incidence of AF 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined risk factors for AF, which could be found using ECG. Interatrial, first-degree atrioventricular (AV), and right bundle branch blocks are reportedly risk factors for the incidence of AF [38][39][40] . ECG measurements and findings, such as PAC, p wave, and LVH, are reportedly risk factors for the incidence of AF 41 .…”
Section: Discussionmentioning
confidence: 99%